Fast Fourier Transform and a Complimentary Filter Based Control of a Robotic System:. Issue 30 (2018) - Kokaj, Agon; Bula, Ines; Dermaku, Artan
Abstract: Fast Fourier transformation (FFT) is a mathematical module that samples signals over a specified time segment. It measures every possible cycle that would include different variables of the system. This paper presents a technique, based in FFT, to evaluate the signals detected by the sensors of a robotic system. Vibrations from the surrounding and noise that is generated, as the robot is at rest or in motion, will disrupt the systems functioning network. The undesired signals or noise that would disrupt our system are removed. This technique enables a better accuracy and reliability in balancing the system and therefore allowing the robot to run smoothly without having disruptions within the system. A linear signal processing and simultaneously analysis of the system is performed.